Study on seed-borne cultivable bacterial diversity and antibiotic resistance of Poa pratensis L. - Xie, Jinjing; Yang, Jie; Zhu, Shaowei; Hou, Xuan; Chen, Haiyan; Bai, Xiaoming; Zhang, Zhenfen (Frontiers in Microbiology, 2024)
In order to study the difference of cultivable seed-borne bacterial diversity between commercial varieties and wild species of Poa pratensis L., and their antibiotic resistance to sulfadiazine, tetracycline, oxytetracycline, ciprofloxacin, gentamicin, oxytetracycline and rifampin. In this study, 60 bacterium isolates were isolated by dilution-coated plate method. Through 16S rRNA sequence analysis, 40 representative isolates with different morphological characteristics were identified and phylogenetic tree was constructed. The results of diversity analysis showed that the seed-borne bacterial diversity of commercial varieties was richer than that of wild species. The antibiotic resistance of the isolated bacterial strains was studied by agar dilution method, and it was concluded that the antibiotic resistance of the seed-borne bacteria carried by commercial varieties was stronger than that of the wild species. Finally, the biofilm formation ability and swimming motility of the bacterial strain were measured, and the correlation between the two and the antibiotic resistance of the bacterial strain was analyzed. The analysis showed that the antibiotic resistance of bacterial strains in Poa pratensis L. was significantly correlated with their swimming motility. In addition, the swimming motility of the bacterial strains was significantly correlated with the biofilm formation ability. It is worth mentioning that this is the first time to study the drug-resistant bacteria distributed in the seed-borne bacteria of Poa pratensis L..